Pathways for Strengthening Lived Experience Leadership for Transformative Systems Change: Reflections on Research and Collective Change Strategies - Mark Loughhead; Ellie Hodges; Heather McIntyre; Nicholas Procter; Anne Barbara; Brooke Bickley; Lee Martinez; Leticia Albrecht; Lisa Huber (Wiley, 2024)
ABSTRACT Introduction The Activating Lived Experience Leadership (ALEL) project was a South Australian participatory action research project that aimed to improve the ways lived experience is recognised, valued and integrated across mental health and social sector systems. ALEL was completed during 2019-2021, where it engaged 182 participants in generating community action and research knowledge. Objective Our paper discusses the project's processes of building a collective partnership among lived experience leaders and other leaders from within the sector, so that the actions and strategies identified through research could be implemented by systems‐level impact. We describe the collaborative process and key learnings that resulted in eight key action areas for transformative systems change in South Australia. Methods The project invited a diverse range of self‐identified lived experience and other leaders to be involved in a PAR process featuring formal qualitative research (focus groups, surveys and interviews) as well as community development activities (leaders' summit meetings, consultations, training and community of practice meetings). These processes were used to help us describe the purpose, achievements and potential of lived experience leadership. Project priorities and systems‐level analysis was also undertaken with lived experience sector leaders and project advisors across two leaders' summit meetings, integrating research outcomes with sector planning to define high‐level actions and a vision for transformational change. Results Participatory action research as informed by systems change and collective impact strategies assisted the project to generate detailed findings about the experiences and complexities of lived experience leadership, and collective responses of how systems could better support, be accountable to and leverage lived experience perspectives, experience and peer‐work approaches. Conclusion Systems change to define, value and embed lived experience leadership benefits from collective efforts in both formal research and sector development activities. These can be used to generate foundational understandings and guidance for working together in genuine ways for transforming mental health and social sector systems, experience and outcomes. Public Contribution Members of lived experience communities codesigned the project, and contributed to project governance and the development of all findings and project reports.